Gender differences in eating disorders - Capuano, Elena Ilaria; Ruocco, Angela; Scazzocchio, Beatrice; Zanchi, Giulia; Lombardo, Camilla; Silenzi, Annalisa; Ortona, Elena; Varì, Rosaria (Frontiers in Nutrition, 2025)
Eating disorders (EDs) are characterized by disturbances in eating behavior and occur worldwide, with a lifetime prevalence of 2 to 5%. Their etiology is complex and multifactorial, involving a complex interplay between genetic, biological, psychological, sociocultural, and environmental factors. They are more common among females than males and may be associated with medical and psychiatric complications, impaired functioning, and decreased quality of life. This narrative review aims at providing an updated contribution to the current understanding of gender differences in eating disorders (EDs) focusing on male population to foster more targeted and effective clinical interventions. A comprehensive review of the scientific literature was conducted by analyzing several major databases, including PubMed, PsycINFO, and Google Scholar. Only in recent years, there has been increased attention on the male population, revealing multiple differences between genders in terms of prevalence, onset, phenomenology, diagnosis, comorbidities, and outcomes of EDs. Moreover, the relationship between different sexual orientations and/or gender identities and EDs is an emerging field of study. Data suggest an increase in eating disorders (EDs) also among the male population underlines the importance that healthcare personnel of all specialties acquire basic competencies for adequately tackling these disorders in a gender perspective. In particular, prevention and early intervention, especially during critical developmental periods like puberty and adolescence, are crucial to avoid permanent damage. Future research and public health initiatives involving schools and families and targeting males should be addressed to promote a healthy relationship with food and body image, reduce stigma, and encourage people to seek help when needed.